Analisis Yuridis Putusan Pengadilan Tata Usaha Negara Nomor 171/G/2024/Ptun.Jkt. Mengenai Gugatan Pembatalan Pencatatan Peralihan Sertipikat Hak Milik - Dias Dhiya Ulhaq; Bambang Heriyanto; Suhermanto Suhermanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the judicial considerations and legal implications of Decision Number 171/G/2024/PTUN.JKT, which concerns a lawsuit seeking the cancellation of the registration of a transfer of freehold title. The analysis highlights how administrative actions in land registration remain a critical aspect of Indonesia’s land governance system, particularly because such actions directly affect legal certainty and the protection of private rights. The research emphasizes that the administrative process of recording land transfer is not merely procedural but constitutes an authoritative decision that can be judicially reviewed when alleged to violate statutory provisions. Through doctrinal analysis, the study evaluates the court’s reasoning regarding the legality, accuracy, and administrative propriety of the official’s actions in light of agrarian regulations and general principles of good governance. The findings suggest that judicial oversight plays an essential role in ensuring that land administration officials exercise their authority responsibly and within the bounds of the law. This decision ultimately reinforces the importance of accountability, precision, and transparency in maintaining an orderly and trustworthy land registration system.